Atypical contact lens related corneal ulcer caused by Pasteurella Multocida - Fatin Hanisah F; Umi Kalthum Md Noh; Rona Asnida Nasaruddin; Jemaima Che Hamzah (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
A 55-year-old healthy lady with history of regular contact lens (CL) use presented with 10 days history of progressive left eye blurring of vision, redness and pain. There was good CL hygiene practiced with no history of swimming, trauma or contact with domestic pets. Left eye vision was hand movement and right eye was 1/60, pinhole 6/18. On the left eye, there was a central, oval-shaped corneal infiltrate with an overlying large epithelial defect and stromal oedema, with significant anterior chamber cells and fibrin. B-mode ultrasound showed no vitritis. Intensive topical benzylpenicillin 10000iu/ml and topical gentamycin 1.4% hourly, homatropine 2% three times daily, oral doxycycline and oral ascorbic acid were started. The gram stain results showed gram positive cocci growth. Her ulcer improved with the treatment and preservative-free dexamethasone 0.1% once daily was commenced to reduce inflammation and scarring. Interestingly, culture was reported as Pasteurella maltocida, a gram negative bacilli sensitive to penicillin, and so treatment was continued until the ulcer completely healed. She had central corneal scarring with best corrected vision of 6/24 in the left eye but was not keen on further surgery to improve her vision. Although it has not been previously reported, Pasteurella multocida can cause CL related corneal ulcer with severe anterior chamber inflammation. This diagnosis should be considered even if there is trivial contact or no history of exposure to domestic animals.